Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO267 - Mark D Hannington; Heidrun Kopp; Nico Augustin; Ingo Klaucke; Anne-Cathrin Wölfl (PANGAEA, 2021)
Multibeam bathymetry raw data was recorded in the Pacific during cruise SO267 that took place between 2018-12-11 and 2019-01-26. The data was collected using the ship extquotesingles own Kongsberg EM 122. Sound velocity profiles (SVP) were applied on the data for calibration. SVP data are part of this dataset publication. This data is part of the DAM (German Marine Research Alliance) underway research data project.